Implementation of the Talent Show Program to Increase Student Self-Confidence at SD Negeri 1 Singosaren - Ningsih, Ema Trya; Nuraini,; Rizkiana, Afitria (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The talent show program is a strategy aimed at developing students' potential, particularly in enhancing their self-confidence in public speaking. This study aims to analyze the implementation of the talent show program at SD Negeri 1 Singosaren and its impact on students' self-confidence. The research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the program has a positive impact on improving students' self-confidence, communication skills, and motivation to learn. Support from the school, parents, and regular practice was identified as key factors contributing to the success of the program. Challenges encountered include the limited availability of professional mentors and the limitations on practice time. The program has proven effective in shaping students' personalities and preparing them to face future challenges with confidence. Recommendations include increasing the intensity of practice sessions and ensuring continued support from both the school and parents.